3D reconstruction and fiber quantification in the pig lower esophageal sphincter region using in vitro diffusion tensor imaging. (8th January 2018) - Liao, Donghua; Gregersen, Hans; Agger, Peter; Laustsen, Christoffer; Ringgaard, Steffen; Stødkilde-Jørgensen, Hans; Zhao, Jingbo
Abstract: Background and aims . The lower esophageal sphincter (LES) regulates transport of ingested substances from the esophagus to the stomach. However, little is known about the muscle fiber spatial arrangement. Diffusion tensor magnetic resonance imaging (DT-MRI) can reveal microscopic details about tissue architecture. The aim of this study was to quantitatively describe the muscle fiber arrangement in the 3D model of the LES region. Methods . A 50 kg pig was used. After tissue fixation, a 7 × 7 × 7 cm 3 tissue sample of the distal esophagus, the proximal stomach, and the diaphragmatic crura was prepared for DT-MRI scanning. The fiber angles were computed in the LES region. Results . The fibers were distributed heterogeneously across the muscle layer of the LES region. In the proximal LES region, the fibers showed a helical crossing pattern with fiber angles ±77.3 to about ±15.0° from longitudinal muscle layer (LM) to circumferential muscle layer (CM). The gastroesophageal flap valve (GEV) was found in the distal LES region and the fibers throughout the GEV were circumferentially distributed. In the distal LES region excluding the GEV, the muscle fibers transferred from axial direction with fiber angle distribution peaks at ±72.5 in LM to the oblique direction with fiber angles peaks at −47.3° in CM. Conclusions . This is the first study that quantitatively demonstrated the smooth muscle fiber distributions in the lower esophagus and the fiber transition through the wall. The results on the myoarchitecture structure from this study will be useful for future LES computational modeling analysis.